Diagnostics and experimental analysis of 3D printed concrete structural elements - Velát, Matěj; Schmid, Pavel; Daněk, Petr; Dvořák, Richard; Hrabová, Kristýna (My University, 2026)
This study investigates the structural behaviour of elements produced by extrusion-based 3D concrete printing (3DCP). Six full-scale columns with intentional imperfections were tested in three-point bending and subsequently analysed through fragment testing. Compressive strength (16.6–32.2 MPa), flexural tensile strength (1.96 MPa parallel vs. 1.27 MPa perpendicular), ultrasonic pulse velocity, bulk density, and water absorption were measured. The results confirmed pronounced anisotropy and strong correlations between physical and mechanical properties. A simplified FEM model, calibrated with fragment data, reproduced global stiffness but not brittle delamination. The combined methodology offers a basis for diagnostics and quality control of 3DCP elements.
Keywords: 3D concrete printing (3DCP); Non-destructive testing (NDT); Mechanical properties; Anisotropy